A computer-based total productive maintenance model for electric motors. (1st January 2014) - Muniswamy, Aruna; Gopalakrishnan, Bhaskaran; Chaudhari, Subodh; Jaridi, Majid; Crowe, Ed; Gupta, Deepak
The paper describes the development of a computer-based total productive maintenance (TPM) model to improve electrical motors readiness and uptime while reducing capital overhead. The TPM model includes the consideration of reactive, periodic, and predictive practices. The input data is processed and the generated report details a set of periodic recommendations providing guidelines on recommended actions and their frequency. The details about test results indicating the current condition of the motor as well estimated reactive, periodic, and predictive maintenance cost details are presented. Based on the historic data stored in its database, the model can predict potential problems prior to failure as well as prescribe periodic maintenance actions to maximise motor life. The TPM model will be a useful tool to predict the degradation in motor life due to deterioration in insulation, bearing, rotor bar and stator windings of the motor.